Prognostic impact of incident left ventricular systolic dysfunction after myocardial infarction - Yoshioka, Goro; Tanaka, Atsushi; Watanabe, Nozomi; Nishihira, Kensaku; Natsuaki, Masahiro; Kawaguchi, Atsushi; Shibata, Yoshisato; Node, Koichi (Frontiers in Cardiovascular Medicine, 2022)
Introduction We sought to investigate the prognostic impact of incident left ventricular (LV) systolic dysfunction at the chronic phase of acute myocardial infarction (AMI). Materials and methods Among 2,266 consecutive patients admitted for AMI, 1,330 patients with LV ejection fraction (LVEF) ≥ 40% during hospitalization who had LVEF data at 6 months after AMI were analyzed. Patients were divided into three subgroups based on LVEF at 6 months: reduced-LVEF (<40%), mid-range-LVEF (≥ 40% and < 50%) and preserved-LVEF (≥ 50%). Occurrence of a composite of hospitalization for heart failure or cardiovascular death after 6 months of AMI was the primary endpoint. The prognostic impact of LVEF at 6 months was assessed with a multivariate-adjusted Cox model. Results Overall, the mean patient age was 67.5 ± 11.9 years, and LVEF during initial hospitalization was 59.4 ± 9.1%. The median (interquartile range) duration of follow-up was 3.0 (1.5–4.8) years, and the primary endpoint occurred in 35/1330 (2.6%) patients (13/69 [18.8%] in the reduced-LVEF, 9/265 [3.4%] in the mid-range-LVEF, and 13/996 [1.3%] in the preserved-LVEF category). The adjusted hazard ratio for the primary endpoint in the reduced-LVEF vs. mid-range-LVEF category and in the reduced-LVEF vs. preserved-LVEF category was 4.71 (95% confidence interval [CI], 1.83 to 12.13; p < 0.001) and 14.37 (95% CI, 5.38 to 38.36; p < 0.001), respectively. Conclusion Incident LV systolic dysfunction at the chronic phase after AMI was significantly associated with long-term adverse outcomes. Even in AMI survivors without LV systolic dysfunction at the time of AMI, post-AMI reassessment and careful monitoring of LVEF are required to identify patients at risk.